2015
DOI: 10.1007/s10661-015-4875-x
|View full text |Cite
|
Sign up to set email alerts
|

Cyanotoxin bioaccumulation in freshwater fish, Washington State, USA

Abstract: Until recently, exposure pathways of concern for cyanotoxins have focused on recreational exposure, drinking water, and dermal contact. Exposure to cyanotoxins through fish consumption is a relatively new area of investigation. To address this concern, microcystins and other cyanotoxins were analyzed in fish collected from nine Washington lakes with recurrent toxic blooms using two types of enzyme-linked immunosorbent assays (ELISAs) and liquid chromatography/mass spectrometry/mass spectrometry (LC-MS/MS). Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 45 publications
0
19
0
2
Order By: Relevance
“…The analytical method used is likely extremely important in influencing the observed toxin concentration in fish. Different concentrations of MCs from the same sample have been previously detected with different analysis methods (e.g., Gkelis et al, 2006;Hardy et al, 2015). Comparison of MC concentrations in different organisms is difficult due to the variety of methods employed, protein binding affinity, and differences in pharmacokinetics in different organisms (Adamovskỳ et al, 2007;Zhang et al, 2013b).…”
Section: Lc-ms/ms Gc-ms;mentioning
confidence: 99%
“…The analytical method used is likely extremely important in influencing the observed toxin concentration in fish. Different concentrations of MCs from the same sample have been previously detected with different analysis methods (e.g., Gkelis et al, 2006;Hardy et al, 2015). Comparison of MC concentrations in different organisms is difficult due to the variety of methods employed, protein binding affinity, and differences in pharmacokinetics in different organisms (Adamovskỳ et al, 2007;Zhang et al, 2013b).…”
Section: Lc-ms/ms Gc-ms;mentioning
confidence: 99%
“…There is also mounting evidence of chronic health problems associated with MC exposure, including a higher incidence of non-alcoholic liver cancer [16,17,18,19]. More recently, MCs have been shown to transfer up the pelagic food chain to fish [20], with additional long-term implications for human health [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The main route of human exposure to MC-LR is the ingestion of contaminated water and/or food. Fish food products are considered the main vectors of cyanotoxins (Hardy et al, 2015, Ni et al, 2015; nevertheless, toxin transfer may also occur with consumption of horticultural products. Indeed, several studies have already reported the accumulation of MCs in agricultural food products (Corbel et al, 2014a, Romero-Oliva et al, 2014 and suggest the use of surface water contaminated with MC-LR as the main cause of contamination.…”
Section: Introductionmentioning
confidence: 99%